A review of Philippine reorganization - Deapera, Lilybeth R.; Gonzalez, Joaquin L., III (1987)
Reorganization and administrative reforms in government, although a necessity, have been a source of frustration, disillusionment, and more problems. The period of reform takes off with a heavy accent on American styles and philosophies which have been disseminated through agencies and institutions in charge of planning and implementation of government reorganization and administrative reforms. Four suggestions are raised for consideration in future reorganization and administrative reform. They are: (1) the objectives, principles, and framework of reorganization must be made clear and simple; (2) continuing incremental/ step by step approach must be employed; (3) participation by representatives from the government departments and agencies, the general public, private and academic sectors must be insured; and (4) political support, will, and timing must be wholehearted and precise.
Keywords: Administrative reform; Presidential Commission on Government Reorganization (PCGR); Government agency reorganization